IoT-Based Occupancy Display System in Office - Aidil, Siti Balqish; Masek, Alias (Research and Innovation in Technical and Vocational Education and Training, 2022)
A structured organization consisted of management personnel is important for an educational institution as each personnel has to carry out their responsibility to achieve the goals set for each department. However, most of the management personnel in Faculty of Technical and Vocational Education (FPTV) at Universiti Tun Hussein Onn Malaysia (UTHM) also worked as a lecturer which requires them to manage their time with lectures and meetings. As this leads to the inflexibility of their schedule, it is difficult for any students to set up a personal appointment with them especially for the final-year students. In any case of emergency leave without early notice from these personnel, students are then left waiting in front of their office. Thus, the purpose of developing this project is to provide an informative board on each office of the personnel that is equipped with display to regularly update on their occupancy status. Thus, the Waterfall model is used to identify and analyze the requirements needed by the respondents on this project. Based on the developed prototype of using NodeMCU ESP8266 Wi-Fi Module as the microcontroller, the system is able to detect motion through the output sent by PIR motion sensor when the room is occupied which was displayed through I2C LCD and LED while a pop-up notification is sent to Blynk application when the system did not detect any motion after the specified delay time. The validation of this project has been collected from several experts within relevant field where the future suggestions for improvements include the installation of ESP 32-CAM on the system.